2011
DOI: 10.1108/17471111111114558
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental sustainability in the clothing industry: a case study of a fair trade retailer

Abstract: Purpose -The purpose of this paper is to assess the issues currently involved in social and environmental sustainability in the clothing industry.Design/methodology/approach -The paper adopts a case study approach to investigate a business that operates successfully in this challenging market.Findings -As a consequence of increasing demand for ethical clothing, it has become standard practice for UK clothing retailers to develop CSR policies which impact upon their methods of garment sourcing and partnerships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 26 publications
0
101
0
3
Order By: Relevance
“…Forty-five relevant papers appearing in focal company categories. [71] x 0 x 0 x x Lueg et al [66] x 0 x x x x Shaw et al [84] 0 0 x 0 0 x Park-Poaps und Rees [65] 0 x 0 x 0 0 Kozlowski et al [99] 0 0 0 0 0 x Milne et al [67] 0 x 0 x x x Sancha et al [13] 0 0 x x x 0 Bhaduri & Ha-Brookshire [100] 0 0 0 0 0 x Egels-Zandén und Hyllman [76] 0 0 x 0 0 0 Dargusch und Ward [90] x x x x 0 0 Curwen et al [92] x x x x 0 0 Carrigan et al [82] x x x x 0 0 Burchielli et al [75] 0 0 x x 0 x Ansett [86] 0 0 0 x x x Goworek [93] 0 x x x 0 x Svensson [95] 0 x 0 x x x Iwanow et al [83] 0 0 0 x x x Börjeson et al [96] x x 0 x 0 0 Giannakis & Papadpoulos [24] x x x x x x de Brito et al [43] x 0 x x 0 0 Perry et al [101] 0 0 0 0 0 0 Locke, Qin et al [97] x 0 x x x x Egels-Zanden & Lindholm [59] x 0 0 x x 0 Locke, Kochan et al [69] x 0 x x 0 x Merk [73] x 0 x x 0 0 MacCarthy & Jayarathne [91] 0 0 x x x 0 Baskaran et al [98] 0 0 0 0 x 0 Anner [68] 0 0 0 x x 0 Miller & Williams [78] 0 0 0 x 0 0 Locke et al [72] x x x x x 0 Yu [80] x 0 0 x 0 0 Hoang & Jones [89] x 0 0 x 0 0 Mamic [94] x x 0 x x x Appendix D [71] 0 0 x 0 Lueg et al [66] 0 0 x 0 Shaw et al [84] 0 0 0 0 Park-Poaps und Rees [65] 0 0 0 0 Kozlowski et al [99] 0 0 0 0 Milne et al …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Forty-five relevant papers appearing in focal company categories. [71] x 0 x 0 x x Lueg et al [66] x 0 x x x x Shaw et al [84] 0 0 x 0 0 x Park-Poaps und Rees [65] 0 x 0 x 0 0 Kozlowski et al [99] 0 0 0 0 0 x Milne et al [67] 0 x 0 x x x Sancha et al [13] 0 0 x x x 0 Bhaduri & Ha-Brookshire [100] 0 0 0 0 0 x Egels-Zandén und Hyllman [76] 0 0 x 0 0 0 Dargusch und Ward [90] x x x x 0 0 Curwen et al [92] x x x x 0 0 Carrigan et al [82] x x x x 0 0 Burchielli et al [75] 0 0 x x 0 x Ansett [86] 0 0 0 x x x Goworek [93] 0 x x x 0 x Svensson [95] 0 x 0 x x x Iwanow et al [83] 0 0 0 x x x Börjeson et al [96] x x 0 x 0 0 Giannakis & Papadpoulos [24] x x x x x x de Brito et al [43] x 0 x x 0 0 Perry et al [101] 0 0 0 0 0 0 Locke, Qin et al [97] x 0 x x x x Egels-Zanden & Lindholm [59] x 0 0 x x 0 Locke, Kochan et al [69] x 0 x x 0 x Merk [73] x 0 x x 0 0 MacCarthy & Jayarathne [91] 0 0 x x x 0 Baskaran et al [98] 0 0 0 0 x 0 Anner [68] 0 0 0 x x 0 Miller & Williams [78] 0 0 0 x 0 0 Locke et al [72] x x x x x 0 Yu [80] x 0 0 x 0 0 Hoang & Jones [89] x 0 0 x 0 0 Mamic [94] x x 0 x x x Appendix D [71] 0 0 x 0 Lueg et al [66] 0 0 x 0 Shaw et al [84] 0 0 0 0 Park-Poaps und Rees [65] 0 0 0 0 Kozlowski et al [99] 0 0 0 0 Milne et al …”
Section: Discussionmentioning
confidence: 99%
“…Park-Poaps and Rees [65] summarize the internal orientation as an "organizational culture in which the organizational core values address principles of fair labour management and the values are reflected on the company's internal alignments and actions". It is suggested that CSR practices can be much more effective when embedded to a company's "ethos and practice" and merely implementing codes of conduct is not enough [82,93,94]. One resulting positive effect can be the reconsideration of the sourcing policies of the buying companies in the form of avoiding orders in countries with poor labor records and exaggerated production deadlines and lead times, as the reader will note later in the supplier barrier section of this paper.…”
Section: Enablersmentioning
confidence: 99%
See 3 more Smart Citations